Prevalence of mental health morbidity among the inmates of childcare homes under Social Justice Department, Government of Kerala - Mohan, Minu; Anilkumar, Thekkethayyil Viswanathan; Mathew, Thomas (International Journal Of Community Medicine And Public Health, 2021)
Background: Mental disorders are common, affecting more than 25% of all people at some time during their lives. Worldwide literature has shown that onset of common mental disorders occurs in childhood and adolescence. Children with mental health problems are often first seen and first treated in the education, social justice, or juvenile justice systems. In India, according to Juvenile Justice Act, 2000, such children are institutionalized in children’s and observation homes under Social Justice Department. This study aims at assessing the mental health status and estimating the prevalence of mental health morbidity among these children and adolescents. Methods: This is a cross sectional study conducted among the inmates of childcare homes under the Social Justice Department, Government of Kerala. Each individual district in the state was fixed as clusters. Out of the 14 districts, five districts were randomly selected. The childcare homes in each cluster were included. All the eligible children in the cluster during the visit were studied. Results: The median SDQ total score of the study participants was 15 (11, 21). The prevalence of mental health morbidity was estimated as 33.3% (95% CI: 26.86% - 40.31%) in the study population. There were 32 (15.9%) study participants with borderline SDQ score. Conclusions: The prevalence in the current study was more than that found in the general child population children across the world as well as in India, which in turn suggests the need of special care needed for these children and adolescents, especially in mental health.